Studies on Im-3-type KSbO3 using high pressure X-ray diffraction and Raman spectroscopy. Issue 3 (3rd July 2018) - Zhao, Huifang; Tan, Dayong; Tian, Yu; He, Yunhong; Li, Yanchun; Li, Xiaodong; Yang, Ke; Chen, Bin; Xiao, Wansheng
ABSTRACT: In situ X-ray diffraction and Raman scattering experiments using a diamond anvil cell revealed that I m-3-type KSbO3 remains stable up to 40.5 GPa with a bulk modulus K 0 = 101.6 (7) GPa. Rietveld structure refinements and mode Grüneisen parameters suggested that the stability mechanism of this three-dimensional cubic tunnel structure was attributed to the isotropic compression for all types of Sb–O bonding in the unit of SbO6 octahedron. Isotropic structure adjustment with external pressure reflected the nature that I m-3-type KSbO3 model structure has a high ionic tolerance with a change in the chemical pressure in the isomorphous substitutions.